Diversity of High-Level Plant in Unaamenda Village, Kolaka Regency - Agistiani, Agistiani; Romadani, Sofia; Amanda, Sekar Aulia; Ulfaidah, Ulfaidah; Sapriana, Sapriana; Rahiki, Rezki Septiya Ningsih; Wulandari, Prety; Maretik, Maretik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
A greater variety of plant species is essential for sustaining the balance of ecosystems and aiding community health. Nonetheless, data regarding the composition and diversity of higher plant life in Unaamenda Village, located in the Wundulako District of Kolaka Regency, remains insufficient. This study aims to identify higher plant species and analyze their diversity levels. The study employed a descriptive observation method through direct observation at three research stations using transect and sample plot techniques. The data obtained were analyzed using the Shannon-Wiener diversity index (H’), relative abundance (KR), evenness index (e), and dominance index (C). The results showed that the diversity index (H’) values at all stations were in the moderate category, indicating a fairly diverse and relatively stable plant community. The evenness index (e) was high, indicating an even distribution of individuals between species, while the dominance index (C) ranged from low to moderate, indicating the absence of excessively dominant species. Species with the highest relative abundance values include banana (Musa paradisiaca), cocoa (Theobroma cacao), pepper (Piper nigrum), and langsat (Lansium domesticum). Environmental conditions, such as temperature and soil pH, are within a range that supports the growth of various plant species. It was concluded that the higher plant vegetation in Unaamenda Village has a moderate level of diversity with an even and relatively stable species composition. The results of this study can serve as a basis for efforts to manage, conserve, and utilize biological resources sustainably in the region.